The debt challenge in Europe - Alan Ahearne; Guntram B. Wolff (Bruegel, 2012)
The euro area faces a double challenge: debt overhang and the need for price adjustment. This paper reviews the debt challenges in the household and corporate sectors and maps out some policy options. In particular, we document the increase in private debt prior to the crisis and consider how the corporate and household sectors have adjusted their balance sheets during the crisis. We examine previous experiences with corporate and household deleveraging and draw lessons for policymakers. We show how the macroeconomic effects of balance-sheet adjustments have been in part offset by the use of fiscal deficits, and we discuss the resulting challenges. A key lesson is the importance of maintaining economic growth and avoiding a prolonged double-dip recession in the euro area while facilitating necessary deleveraging in some over-indebted sectors and countries. We also emphasise the need for a growth strategy tailored to southern Europe.
Keywords: 330; Private Verschuldung; Verbindlichkeiten; Kaufkraftparität; Öffentliche Schulden; EU-Staaten